How Different Is the Cyclical Behavior of Home Production Across Countries? - Kose, Ayhan (IMF Working Papers; Working Paper ;, 2006)
This paper studies stylized business cycle properties of household production in four industrialized countries (Canada, the United States, Germany, and Japan). We employ a dynamic small open economy business cycle model that incorporates a household production sector. We use the model to generate data on home output, hours worked in the home sector, and hours spent on leisure. We find that in each country, home output is more volatile than market output while home sector hours are about as volatile as those in the market sector. In each country, leisure is the least volatile series. Leisure hours and home hours are countercyclical in all countries, and home output is not highly correlated with market output. Home sector variables are generally less persistent than market variables, and cross-country correlations related to home production tend to be lower than those related to market production. These findings demonstrate that despite some well-known structural differences in labor markets, the cyclical features of home sector variables are similar across the countries we consider.